Modeling of a selective solar absorber thin film structure based on double TiNxOy layers for concentrated solar power applications. (15th January 2017) - Zhang, J.; Chen, T.P.; Liu, Y.C.; Liu, Z.; Yang, H.Y.
Highlights: Dielectric function of TiNx Oy is modeled with one Drude and two Lorentz terms. Optical properties of the different N/O ratios TiNx Oy are studied with ellipsometry. With low and high N/O ratio TiNx Oy, a selective solar absorber is demonstrated. Abstract: By using double TiNx Oy absorption layers with low N/O ratio (TiNO_L) and high N/O ratio (TiNO_H), a spectral selective solar absorber (SSA) with the structure of SiO2 -TiO2 -TiNO_L-TiNO_H-Cu has been proposed. Optical properties of the TiNO_L and TiNO_H layers are investigated with spectroscopic ellipsometry (SE) in the wavelength range of 0.3–2.5 μm using an optical dispersion model in which the absorption mechanisms in TiNx Oy including the localized surface plasmon resonance (LSPR), free electron absorption and interband transitions are taken into account. Because TiNO_H has a higher free electron concentration than that of TiNO_L, the absorption due to both the LSPR and free electron absorption in TiNO_H is found larger than that in TiNO_L. With the model parameters of the dispersion model obtained from the SE modeling, the reflectance spectrum of the SSA in the wide wavelength range of 0.3–25 μm covering both the solar radiation and heat radiation of a hot surface has been simulated; and the simulated result agrees well with the experimental result.